S-100b protein levels as a predictor for long-term disability after head injury. Issue 12 (18th November 2005) - Lomas, John-Paul; Dunning, Joel
Abstract : A short cut review was carried out to establish whether levels of S-100b were predictive of long-term disability after head injury. 200 papers were found using the reported searches, of which 12 presented the best evidence to answer the clinical question. The author, date, and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these best papers are tabulated. It is concluded that a raised level of S-100b is a marker of poorer long-term outcome after both major and minor head injury.